Pengaruh Pengenalan Lapangan Persekolahan dan Soft Skill Terhadap Kesiapan Menjadi Guru Pada Mahasiswa Prodi Pendidikan Ekonomi - Krisma Periti Sinta; Kadori Haidar; Riyo Riyadi (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to determine whether PLP affects teacher readiness in economics education study program students, whether soft skills affect teacher readiness in economic education study program students and whether PLP and soft skills simultaneously affect teacher readiness in economic education study program students. This research uses a quantitative approach with the type of explanatory research. The population in this study is students of the Economic Education Study Program of Mulawarman University, Class of 2020. The sampling technique uses the Saturated Sample Technique with a total of 66 people. The data collection technique carried out is a questionnaire. The results showed that thitung > ttable, namely thitung > ttable, which is 5,086> 1,997 and significance 0.000 < 0.05, then the PLP variable partially has a positive and significant influence on readiness to become a teacher of economic education students and the results of tcalculate > ttable, which is 8,030 > 1,997 and the significance of 0.000 < 0.05 on soft skill variables partially has a positive and significant influence on readiness to become a teacher of economic education students. Simultaneously, PLP and soft skills have a significant effect, amounting to 51,772 fcalculate > 1,997 ftabel on readiness to become teachers in economic education students.